PELANGGARAN MAKSIM KERJA SAMA GRICE DAN IMPLIKATUR PERCAKAPAN DALAM PERISTIWA TUTUR PERSIDANGAN KASUS PEMBUNUHAN MIRNA - Miftahul Ulum; Asep Muhyidin (Prakata: Jurnal Bahasa dan Sastra Indonesia Serta Pembelajaran, 2024)
The research questions are: (1) What are the types of violations maxims of quantity and the implications of speech acts in the trial of the murder case in the Central Jakarta District Court? (2) What are the types of violations maxims of quality and the implications of speech acts in the trial of the murder case in the Central Jakarta District Court? (3) What are the types of violations maxims of the relevance and implications of speech acts in the trial of the murder case in the Central Jakarta District Court? and (4) What are the types of violations maxims of manner and implications of speech acts in the trial of the murder case in the Central Jakarta District Court? The method in this research uses descriptive method. Data collection techniques using literature review techniques, listening techniques and note taking techniques